2.2.41 Problems 4001 to 4100

Table 2.83: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

4001

\[ {}x y^{\prime \prime }-\left (x -1\right ) y^{\prime }-x y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.763

4002

\[ {}\left (2 x^{2}+1\right ) y^{\prime \prime }+7 y^{\prime } x +2 y = 0 \]
i.c.

[[_2nd_order, _with_linear_symmetries]]

0.614

4003

\[ {}4 y^{\prime \prime }+y^{\prime } x +4 y = 0 \]
i.c.

[_Lienard]

0.516

4004

\[ {}y^{\prime \prime }+2 x^{2} y^{\prime }+x y = 2 \cos \left (x \right ) \]

[[_2nd_order, _linear, _nonhomogeneous]]

0.679

4005

\[ {}y^{\prime \prime }+y^{\prime } x -4 y = 6 \,{\mathrm e}^{x} \]

[[_2nd_order, _linear, _nonhomogeneous]]

0.604

4006

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{1-x}+x y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.662

4007

\[ {}x^{2} y^{\prime \prime }+\frac {x y^{\prime }}{\left (-x^{2}+1\right )^{2}}+y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.764

4008

\[ {}\left (x -2\right )^{2} y^{\prime \prime }+\left (x -2\right ) {\mathrm e}^{x} y^{\prime }+\frac {4 y}{x} = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.763

4009

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x \left (x -3\right )}-\frac {y}{x^{3} \left (x +3\right )} = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.145

4010

\[ {}x^{2} y^{\prime \prime }+x \left (1-x \right ) y^{\prime }-7 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.066

4011

\[ {}4 x^{2} y^{\prime \prime }+x \,{\mathrm e}^{x} y^{\prime }-y = 0 \]

[[_Emden, _Fowler]]

1.024

4012

\[ {}4 x y^{\prime \prime }-y^{\prime } x +2 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.183

4013

\[ {}x^{2} y^{\prime \prime }-x \cos \left (x \right ) y^{\prime }+5 \,{\mathrm e}^{2 x} y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.975

4014

\[ {}4 x^{2} y^{\prime \prime }+3 y^{\prime } x +x y = 0 \]

[[_Emden, _Fowler]]

0.828

4015

\[ {}6 x^{2} y^{\prime \prime }+x \left (1+18 x \right ) y^{\prime }+\left (1+12 x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.886

4016

\[ {}x^{2} y^{\prime \prime }+y^{\prime } x -\left (x +2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.009

4017

\[ {}2 x y^{\prime \prime }+y^{\prime }-2 x y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.734

4018

\[ {}3 x^{2} y^{\prime \prime }-x \left (x +8\right ) y^{\prime }+6 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.921

4019

\[ {}2 x^{2} y^{\prime \prime }-x \left (2 x +1\right ) y^{\prime }+2 \left (4 x -1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.920

4020

\[ {}x^{2} y^{\prime \prime }+x \left (1-x \right ) y^{\prime }-\left (5+x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.020

4021

\[ {}3 x^{2} y^{\prime \prime }+x \left (7+3 x \right ) y^{\prime }+\left (1+6 x \right ) y = 0 \]

[[_2nd_order, _exact, _linear, _homogeneous]]

0.886

4022

\[ {}x^{2} y^{\prime \prime }+y^{\prime } x +\left (1-x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.786

4023

\[ {}3 x^{2} y^{\prime \prime }+x \left (3 x^{2}+1\right ) y^{\prime }-2 x y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.899

4024

\[ {}4 x^{2} y^{\prime \prime }-4 x^{2} y^{\prime }+\left (2 x +1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.845

4025

\[ {}x^{2} y^{\prime \prime }+x \left (3-2 x \right ) y^{\prime }+\left (1-2 x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.851

4026

\[ {}x^{2} y^{\prime \prime }-x \left (x +3\right ) y^{\prime }+\left (4-x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.891

4027

\[ {}x^{2} y^{\prime \prime }+x \left (3-x \right ) y^{\prime }+y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.828

4028

\[ {}x^{2} y^{\prime \prime }+y^{\prime } x -\left (4+x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.307

4029

\[ {}x^{2} y^{\prime \prime }-\left (-x^{2}+x \right ) y^{\prime }+\left (x^{3}+1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.902

4030

\[ {}x^{2} y^{\prime \prime }-\left (2 \sqrt {5}-1\right ) x y^{\prime }+\left (\frac {19}{4}-3 x^{2}\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.149

4031

\[ {}x^{2} y^{\prime \prime }+\left (-2 x^{5}+9 x \right ) y^{\prime }+\left (10 x^{4}+5 x^{2}+25\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.877

4032

\[ {}x^{2} y^{\prime \prime }+\left (4 x +\frac {1}{2} x^{2}-\frac {1}{3} x^{3}\right ) y^{\prime }-\frac {7 y}{4} = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.538

4033

\[ {}x^{2} y^{\prime \prime }+x^{2} y^{\prime }+x y = 0 \]

[[_2nd_order, _with_linear_symmetries], [_2nd_order, _linear, ‘_with_symmetry_[0,F(x)]‘]]

1.187

4034

\[ {}x^{2} y^{\prime \prime }+x \left (x -3\right ) y^{\prime }+\left (4-x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.870

4035

\[ {}4 x^{2} y^{\prime \prime }+2 x^{2} y^{\prime }+y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.902

4036

\[ {}x^{2} y^{\prime \prime }+x \cos \left (x \right ) y^{\prime }-2 y \,{\mathrm e}^{x} = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.169

4037

\[ {}x^{2} y^{\prime \prime }+x^{2} y^{\prime }-\left (x +2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.924

4038

\[ {}x^{2} y^{\prime \prime }+2 x^{2} y^{\prime }+\left (x -\frac {3}{4}\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.914

4039

\[ {}x^{2} y^{\prime \prime }+y^{\prime } x +\left (2 x -1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.306

4040

\[ {}x^{2} y^{\prime \prime }+x^{3} y^{\prime }-\left (x +2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.319

4041

\[ {}x^{2} \left (x^{2}+1\right ) y^{\prime \prime }+7 x \,{\mathrm e}^{x} y^{\prime }+9 \left (1+\tan \left (x \right )\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.403

4042

\[ {}x^{2} \left (x +1\right ) y^{\prime \prime }+x^{2} y^{\prime }-2 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.981

4043

\[ {}x^{2} y^{\prime \prime }+3 y^{\prime } x +\left (1-x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.828

4044

\[ {}x y^{\prime \prime }-y = 0 \]

[[_Emden, _Fowler]]

1.086

4045

\[ {}x^{2} y^{\prime \prime }+x \left (x^{2}+6\right ) y^{\prime }+6 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.904

4046

\[ {}x^{2} y^{\prime \prime }+x \left (1-x \right ) y^{\prime }-y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.891

4047

\[ {}4 x^{2} y^{\prime \prime }+\left (1-4 x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.820

4048

\[ {}x y^{\prime \prime }+y^{\prime }-2 y = 0 \]

[[_Emden, _Fowler]]

0.730

4049

\[ {}x^{2} y^{\prime \prime }+y^{\prime } x -\left (x +1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.294

4050

\[ {}x^{2} y^{\prime \prime }-x \left (x +3\right ) y^{\prime }+4 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.818

4051

\[ {}x^{2} y^{\prime \prime }-x^{2} y^{\prime }-2 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.941

4052

\[ {}x^{2} y^{\prime \prime }-x^{2} y^{\prime }-\left (3 x +2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.353

4053

\[ {}x^{2} y^{\prime \prime }+x \left (5-x \right ) y^{\prime }+4 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.904

4054

\[ {}4 x^{2} y^{\prime \prime }+4 x \left (1-x \right ) y^{\prime }+\left (2 x -9\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.965

4055

\[ {}x^{2} y^{\prime \prime }+2 x \left (x +2\right ) y^{\prime }+2 \left (x +1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.289

4056

\[ {}x^{2} y^{\prime \prime }-x \left (1-x \right ) y^{\prime }+\left (1-x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.803

4057

\[ {}4 x^{2} y^{\prime \prime }+4 x \left (2 x +1\right ) y^{\prime }+\left (4 x -1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.977

4058

\[ {}4 x^{2} y^{\prime \prime }-\left (3+4 x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.252

4059

\[ {}x y^{\prime \prime }-y^{\prime } x +y = 0 \]

[_Laguerre, [_2nd_order, _linear, ‘_with_symmetry_[0,F(x)]‘]]

1.144

4060

\[ {}x^{2} y^{\prime \prime }+x \left (4+x \right ) y^{\prime }+\left (x +2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.344

4061

\[ {}x^{2} y^{\prime \prime }+y^{\prime } x +\left (x^{2}-\frac {9}{4}\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.835

4062

\[ {}x y^{\prime \prime }-y^{\prime }+x y = 0 \]

[_Lienard]

1.114

4063

\[ {}y^{\prime \prime }+x y = 0 \]

[[_Emden, _Fowler]]

0.470

4064

\[ {}y^{\prime \prime }-x^{2} y = 0 \]

[[_Emden, _Fowler]]

0.466

4065

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-6 y^{\prime } x -4 y = 0 \]

[[_2nd_order, _exact, _linear, _homogeneous]]

0.619

4066

\[ {}x y^{\prime \prime }+y^{\prime }+2 y = 0 \]

[[_Emden, _Fowler]]

0.732

4067

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

[_Lienard]

0.733

4068

\[ {}2 x y^{\prime \prime }+5 \left (1-2 x \right ) y^{\prime }-5 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.860

4069

\[ {}x y^{\prime \prime }+y^{\prime }+x y = 0 \]

[_Lienard]

0.614

4070

\[ {}\left (4 x^{2}+1\right ) y^{\prime \prime }-8 y = 0 \]

[[_2nd_order, _exact, _linear, _homogeneous]]

0.587

4071

\[ {}x^{2} y^{\prime \prime }+y^{\prime } x +\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.814

4072

\[ {}4 x y^{\prime \prime }+3 y^{\prime }+3 y = 0 \]

[[_Emden, _Fowler]]

0.798

4073

\[ {}x^{2} y^{\prime \prime }+\frac {3 y^{\prime } x}{2}-\frac {\left (x +1\right ) y}{2} = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.899

4074

\[ {}x^{2} y^{\prime \prime }-x \left (2-x \right ) y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.293

4075

\[ {}x^{2} y^{\prime \prime }-3 y^{\prime } x +4 \left (x +1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.813

4076

\[ {}y^{\prime \prime }+\left (1-\frac {3}{4 x^{2}}\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

1.234

4077

\[ {}5 x y+4 y^{2}+1+\left (x^{2}+2 x y\right ) y^{\prime } = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.529

4078

\[ {}2 x \tan \left (y\right )+\left (x -x^{2} \tan \left (y\right )\right ) y^{\prime } = 0 \]

[[_1st_order, _with_exponential_symmetries]]

1.858

4079

\[ {}y^{2} \left (x^{2}+1\right )+y+\left (2 x y+1\right ) y^{\prime } = 0 \]

[_rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.423

4080

\[ {}4 x y^{2}+6 y+\left (5 x^{2} y+8 x \right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.241

4081

\[ {}5 x +2 y+1+\left (2 x +y+1\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.336

4082

\[ {}3 x -y+1-\left (6 x -2 y-3\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.888

4083

\[ {}x -2 y-3+\left (2 x +y-1\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.648

4084

\[ {}6 x +4 y+1+\left (4 x +2 y+2\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

5.230

4085

\[ {}3 x -y-6+\left (x +y+2\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

13.357

4086

\[ {}2 x +3 y+1+\left (4 x +6 y+1\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.424

4087

\[ {}y = y^{\prime }+\frac {{y^{\prime }}^{2}}{2} \]

[_quadrature]

0.682

4088

\[ {}\left (y-y^{\prime } x \right )^{2} = 1+{y^{\prime }}^{2} \]

[[_1st_order, _with_linear_symmetries], _rational, _Clairaut]

0.589

4089

\[ {}y-x = {y^{\prime }}^{2} \left (1-\frac {2 y^{\prime }}{3}\right ) \]

[[_homogeneous, ‘class C‘], _dAlembert]

0.742

4090

\[ {}x^{2} y^{\prime } = x \left (-1+y\right )+\left (-1+y\right )^{2} \]

[[_homogeneous, ‘class C‘], _rational, _Riccati]

1.846

4091

\[ {}y^{\prime } = {\mathrm e}^{-x} \]

[_quadrature]

0.497

4092

\[ {}y^{\prime } = 1-x^{5}+\sqrt {x} \]

[_quadrature]

0.276

4093

\[ {}3 y-2 x +\left (3 x -2\right ) y^{\prime } = 0 \]

[_linear]

1.875

4094

\[ {}x^{2}+x -1+\left (2 x y+y\right ) y^{\prime } = 0 \]

[_separable]

1.934

4095

\[ {}{\mathrm e}^{2 y}+\left (x +1\right ) y^{\prime } = 0 \]

[_separable]

1.843

4096

\[ {}\left (x +1\right ) y^{\prime }-x^{2} y^{2} = 0 \]

[_separable]

1.632

4097

\[ {}y^{\prime } = \frac {y-2 x}{x} \]

[_linear]

1.593

4098

\[ {}x^{3}+y^{3}-x y^{2} y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

8.413

4099

\[ {}y^{\prime }+y = 0 \]

[_quadrature]

1.372

4100

\[ {}y^{\prime }+y = x^{2}+2 \]

[[_linear, ‘class A‘]]

1.291